2017
DOI: 10.21275/20061703
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis Prevails Staphylococcus aureus in Multispecies Biofilm under Gentamicin Stress

Abstract: Out of 60 staphylococcal isolates isolated form different sources, the results revealed that 20 and 10 were identified as S. aureus and S. epidermidis, respectively. These results were confirmed by detecting 16sRNA gene. Remarkably, 80% of S. aureus and 80% of S. epidrmidis isolates developed Methicillinresistance. Findings of the current work demonstrated that most of methicillin resistant S. aureus (MRSA) and methicillin resistant S. epidermidis (MRSE) formed weak biofilm. The competition between S. aureus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Research results Karam et al (2017), suggest that 80% of S. aureus and 80% of S. epidrmidis isolates developed Methicillin resistance. The findings of the current work have shown that most of the methicillin-resistant S. aureus (MRSA) and methicillin-resistant S. epidermidis (MRSE) formed a weak biofilm.…”
mentioning
confidence: 98%
“…Research results Karam et al (2017), suggest that 80% of S. aureus and 80% of S. epidrmidis isolates developed Methicillin resistance. The findings of the current work have shown that most of the methicillin-resistant S. aureus (MRSA) and methicillin-resistant S. epidermidis (MRSE) formed a weak biofilm.…”
mentioning
confidence: 98%